Trends and mortality effects of vitamin A deficiency in children in 138 low-income and middle-income countries between 1991 and 2013: A pooled analysis of population-based surveys (2015)
Background Vitamin A defi ciency is a risk factor for blindness and for mortality from measles and diarrhoea in children aged 6–59 months. We aimed to estimate trends in the prevalence of vitamin A defi ciency between 1991 and 2013 and its mortality burden in low-income and middle-income countries.